MSME FINANCIAL LITERACY MODEL AS A MEASURING TOOL FOR MSME FINANCIAL PERFORMANCE: Case Study of Bogor, Depok and Kuningan MSMEs - Setiawati, Sri; Gursida, Hari; Indrayono, Yohanes (jfpublisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to the economy but often struggle with financial management due to limited financial literacy. This leads to poor accounting practices and weak financial reporting, hindering growth and competitiveness. The rapid changes of the industrial revolution 4.0 further challenge MSMEs to adapt. This study examines financial literacy’s role in enhancing MSME financial performance in Bogor, Depok, and Kuningan. It identifies key influencing factors and their impact. Using an associative methodology with quantitative and qualitative approaches, data were collected from 399 MSME practitioners via surveys, interviews, and Focus Group Discussions (FGDs). Structural Equation Modeling (SEM) with Partial Least Square (PLS) was used for analysis. Findings show financial behavior, attitude, bank product usage, credit/loans, and financial inclusion positively affect financial performance through financial literacy. However, risk preference and digital literacy had no significant impact. The study underscores the need to improve financial literacy and recommends developing a financial reporting application to help MSMEs manage finances effectively.